Fisetin treatment alleviates kidney injury in mice with diabetes- exacerbated atherosclerosis through inhibiting CD36/fibrosis pathway - Zou Ting-feng; Liu Zhi-gang; Cao Pei-chang; Zheng Shi-hong; Guo Wen-tong; Wang Tian-xiang; Chen Yuan-li; Duan Ya-jun; Li Qing-shan; Liao Chen-zhong; Xie Zhou-ling; Han Ji-hong; et al. (Acta Pharmacologica Sinica; Vol 44, No 10 (October 2023): Acta Pharmacologica Sinica, 2023)
Diabetes-related vascular complications include diabetic cardiovascular diseases (CVD), diabetic nephropathy (DN) and diabetic retinopathy, etc. DN can promote the process of end-stage renal disease. On the other hand, atherosclerosis accelerates kidney damage. It is really an urge to explore the mechanisms of diabetes-exacerbated atherosclerosis as well as new agents for treatment of diabetes-exacerbated atherosclerosis and the complications. In this study we investigated the therapeutic effects of fisetin, a natural flavonoid from fruits and vegetables, on kidney injury caused by streptozotocin (STZ)-induced diabetic atherosclerosis in low density lipoprotein receptor deficient (LDLR−/−) mice. Diabetes was induced in LDLR−/− mice by injecting STZ, and the mice were fed high-fat diet (HFD) containing fisetin for 12 weeks. We found that fisetin treatment effectively attenuated diabetes- exacerbated atherosclerosis. Furthermore, we showed that fisetin treatment significantly ameliorated atherosclerosis-enhanced diabetic kidney injury, evidenced by regulating uric acid, urea and creatinine levels in urine and serum, and ameliorating morphological damages and fibrosis in the kidney. In addition, we found that the improvement of glomerular function by fisetin was mediated by reducing the production of reactive oxygen species (ROS), advanced glycosylation end products (AGEs) and inflammatory cytokines. Furthermore, fisetin treatment reduced accumulation of extracellular matrix (ECM) in the kidney by inhibiting the expression of vascular endothelial growth factor A (VEGFA), fibronectin and collagens, while enhancing matrix metalloproteinases 2 (MMP2) and MMP9, which was mainly mediated by inactivating transforming growth factor β (TGFβ)/SMAD family member 2/3 (Smad2/3) pathways. In both in vivo and in vitro experiments, we demonstrated that the therapeutic effects of fisetin on kidney fibrosis resulted from inhibiting CD36 expression. In conclusion, our results suggest that fisetin is a promising natural agent for the treatment of renal injury caused by diabetes and atherosclerosis. We reveal that fisetin is an inhibitor of CD36 for reducing the progression of kidney fibrosis, and fisetin-regulated CD36 may be a therapeutic target for the treatment of renal fibrosis.